CITIZENSHIP EDUCATION IN STRENGTHENING THE UNITY OF THE NATION - Lily Hidayani (Jurnal Multidisiplin Sahombu, 2022)
In the era of globalization, it is crucial to investigate the existence of thoughts concerning efforts to maintain unity and integrity and strengthen the Indonesian nation's identity. Civic education is one of the efforts done to impart the essential value of patriotism, which must be given to young children as well as the larger community. Determining the role of civic education in an endeavor to build national unity and integrity is the purpose of this study. This post describes a qualitative research technique with a descriptive analysis of the research outcomes. The findings of the study indicate that Citizenship Education is an endeavor to foster patriotism through the transmission of fundamental knowledge and skills understanding the relationship between citizens and the state, as well as Preliminary State Defense Education. By embedding a decent personality in accordance with religious norms and regulations, citizenship education will promote the moral behavior of citizens who are trustworthy, have noble character, are willing to analyze their own performance, and develop themselves autonomously and sustainably